Feasibility Analysis of Industrial Waste Reduction Investment: Potential of Fruit Basket and Mat Products: Analisis Kelayakan Investasi Pengurangan Limbah Industri: Potensi Produk Keranjang Buah dan Keset - Anasrul, Rahmad Fajri; Haryo, Afrido; Tristiadi, Aloysius Kalis; Swilugar, Ayu; Bagaskara, Caesarius Haryo; Vyanti, Jessica (Klabat Journal of Management, 2026)
Unprocessed waste has become a major issue in the world today. In 2021, Indonesia's environmental statistics recorded that approximately 24.5% of the total waste generated was not properly managed. One of the subjects of this issue is palm oil and textiles. Palm oil is a commodity that has experienced rapid growth, with a growth rate of 22.72% from 2017 to 2018. Meanwhile, textile waste is commonly found, especially in garment companies. This research aims to conduct an investment feasibility analysis from a financial perspective for industrial waste reduction, focusing on the business potential of fruit baskets made from palm oil waste and mats made from fabric scraps. The products generated from this waste can provide a sustainable solution while also generating financial profit. Therefore, a feasibility analysis was carried out for these two products. The investment feasibility analysis method is used to evaluate the potential success of these two waste-reducing products. The feasibility analysis involves calculating initial costs, revenue, operational costs, and cash flow projections over a certain period. Additionally, various risk factors and relevant assumptions are also considered in this analysis. The results of the feasibility analysis conclude that the fruit basket made from palm oil waste is more feasible than the mat made from fabric scraps.